Crafting Game-Models using Reactive System Design - Harel, David; Segall, Itai; Kugler, Hillel; Setty, Yaki (Future Play, 2008)
This paper presents a game-model of a gym training system, where the behavior of the system is specified using languages developed originally for reactive system design, which drive a game engine. The approach makes it possible to describe behaviors of different parts of the system using different reactive system design languages and tools. It thus provides a framework for integrating the model behavior to obtain an executable game-model of the entire system. Among the advantages of this approach is the ability to use existing analysis tools to understand the game behavior at design time and run time, the ability to easily modify the behavior, and the use of visual languages to allow various stakeholders to be involved in early stages of building the game. Finally, we suggest integrating future games and game design methods into the emerging field of biological modeling, to which reactive system design has recently been successfully applied.